Covid-19 and Sustainable Architectural Education: Challenges and Perceptions on Online Learning.: Challenges and Perceptions on Online Learning - ALLU-KANGKUM, EVELYN LAMI ASHELO (IJRDO- Journal of Educational Research, 2021)
Architectural education has had its share in the continuous demand for shift in the learning process to address changes and new requirements sustainably. Recently, the impact of coronavirus (covid-19) pandemic has been unpresented in all areas of human activities. In the education section pandemic has forced schools to shut down and thus, the suspension of face-to-face learning to remote or online learning in many countries. This action was taken to mitigate the impact of the coronavirus pandemic and its spread. This study sought the opinion of architectural students across the country’s 6 geopolitical regions in public universities via an online questionnaire survey on the challenges of online or remote learning. This study would help schools of architecture to strategize to reduce the challenges uncovered and promote the potentials of online learning. The main theoretical findings for the potentials of online learning are; flexible technological innovations in teaching and the development of new online tools. Whilst the challenges include; inadequate electricity supply, internet/data affordability, and 3D analogue or physical model presentation and validated. furthermore, the primary findings uncover some challenges common to Nigeria, which includes; unbelief, incapacity and family interruptions. The study from its findings suggests insights into the way forward like harnessing the potentials of solar energy to supply clean energy and electricity to schools of architecture in Nigeria amongst others.